Analisis Perbedaan Profitabilitas Sebelum dan Sesudah Memenangkan Top CSR (Corporate Social Responsibility) - Sixtia Apriyana Asrul; Wiwik Andriani; Eka Rosalina (Jurusan Akuntansi Politeknik Negeri Padang, 2018)
This study aimed to examine whether there are differences in the profitability of a company before and after winning TOP CSR. The data used in this study is secondary data obtained from the financial statements of companies listed on the Indonesia Stock Exchange for the period 2008-2017. The sample of this study consisted of 17 companies using purposive sampling, ie companies that won TOP CSR from 2011-2017, companies listed on the Indonesia Stock Exchange and companies that had issued 3 years of financial statements after winning the CSR TOP. The variable used in this study is profitability which is proxied by Return On Assets (ROA), Return On Equity (ROE) and Net Profit Margin (NPM). Hypothesis testing is carried out by Paired Sample T-test using the IBM SPSS Version 20 software. Based on the tests carried out, it can be concluded that there are differences in profitability as seen from the ROA side, whereas when viewed from the ROE and NPM side it is not there are differences in profitability.